Advances in Tin(II)‐Based Perovskite Solar Cells: From Material Physics to Device Performance. Issue 1 (5th October 2021) - Li, Man; Li, Faming; Gong, Jue; Zhang, Tiankai; Gao, Feng; Zhang, Wen-Hua; Liu, Mingzhen
Abstract : During the past decade, metal halide perovskites are widely studied in the field of optoelectronic materials due to their unique optical and electrical properties. Lead‐based halide perovskite solar cells (PSCs), in particular, currently achieve a record efficiency of 25.5%, thus showing strong potential in industrial application. However, toxicity of lead‐based perovskite materials possesses great concerns to natural environment and human body. Therefore, the quest for nontoxic and eco‐friendly elements to replace lead in perovskites is of great interest. Among all the element choices, tin(II) (Sn 2+ ) is the most promising candidate. As a rising star of lead‐free PSCs, Sn‐based PSCs have drawn much attention and made promising progress during the past few years. While the rapid oxidation and decomposition of Sn‐based perovskites result in poor stability and low efficiency of PSCs. In this review, structural, optoelectronic properties and the critical issues of Sn‐based perovskite materials are analyzed. Then, a detailed discussion on the recent methods in solving critical issues of Sn‐based perovskite devices, from optimization on materials physics to device performance, is also presented. Finally, remaining challenges and future perspective are given to advance the progression of Sn‐based PSCs. Abstract : Despite being a class of promising materials for substituting Pb‐based perovskites, Sn‐based perovskite materials face multiple critical challenges including Sn 2+ ‐to‐Sn 4+ oxidation, intrinsic vacancy formation, kinetically uncontrolled crystallization, and energy level mismatch with conventionally adopted charge transport layers, which require effective approaches to properly mitigate and to achieve further advanced device performance on solar cells.